1992
DOI: 10.1161/01.atv.12.1.120
|View full text |Cite
|
Sign up to set email alerts
|

A definition of the intima of human arteries and of its atherosclerosis-prone regions. A report from the Committee on Vascular Lesions of the Council on Arteriosclerosis, American Heart Association.

Abstract: his report is a concise review of current knowledge of the structure and function of the intima of the aorta and the major distributing arteries. The main purpose of the review is to delineate normal arterial intima from atherosclerotic lesions and, in particular, to distinguish physiological adaptations from atherosclerotic increases in intimal thickness. To characterize normal intima, including the adaptive intimal thickenings, some of which represent locations in which atherosclerotic lesions are prone to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
199
1
9

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(217 citation statements)
references
References 92 publications
(37 reference statements)
8
199
1
9
Order By: Relevance
“…Both disorders have been associated with precocious and accelerated increase in vascular stiffness which, in turn, enhances the risk of cardiovascular diseases and mortality [3,4,5,6]. Peripheral pulse pressure (PP) is regarded as a surrogate measure of arterial stiffness in adult subjects older than 50 years, but not in the young [7, 8,] and in the general population it has been shown to correlate with cardiovascular morbidity and mortality [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Both disorders have been associated with precocious and accelerated increase in vascular stiffness which, in turn, enhances the risk of cardiovascular diseases and mortality [3,4,5,6]. Peripheral pulse pressure (PP) is regarded as a surrogate measure of arterial stiffness in adult subjects older than 50 years, but not in the young [7, 8,] and in the general population it has been shown to correlate with cardiovascular morbidity and mortality [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…By positioning a non-occlusive, soft silicone collar around the rabbit carotid artery, a neo-intima develops within seven days via smooth muscle cell infiltration into the subendothelium (Kockx et al, 1992). A neo-intima can be considered as a site of predilection for atherosclerosis (Wilens, 1951;Stary et al, 1992). Previously, it has been demonstrated that the nitric oxide synthase: guanosine 3':5'-cyclic monophosphate (cyclic GMP) system remains intact in neo-intima-bearing vessels, but that muscarinic endothelium-dependent relaxation becomes selectively impaired (De Meyer et al, 1991;Arthur & Dusting, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Based on their structural differences at different stages of atherogenesis, atherosclerotic plaques are classified as early, intermediate, advanced, and complicated lesions (12)(13)(14). Recently, other variables of the advancing lesions have also been described and related to the structural differences of the plaques.…”
mentioning
confidence: 99%